EVALUATION OF LAND SUITABILITY FOR LIVESTOCK FEED IN THE BOBANE IGO AREA, SOUTH JAILOLO DISTRICT, WEST HALMAHERA REGENCY - Gunawan Hartono; Sulasmi; Idris Abd. Rachman; Robo, Sarif (Journal of Synergy Landscape, 2024)
The availability of quality and sustainable animal feed is very important to support the growth and development of livestock. Problems faced by farmers in West Halmahera Regency include unsustainable availability of animal feed, especially during the dry season, and low-quality animal feed, resulting in low livestock productivity. This research aims to evaluate the suitability of land for animal feed in the Bobane Igo area, South Jailolo District, West Halmahera Regency, with an area of 1684.7 ha. The types of plants studied were lamtoro, calliandra, legumes, and turi. The methods used are field surveys, soil data analysis, and research data analysis using method matching. The research results show that the total area of the Bobane Igo area is 1684.7, indicating that the Bobane Igo area has high potential for developing ruminant animal feed. A total of 1023.4 ha (61%) for calliandra and 1154.2 ha (68%) for legumes. It is hoped that the development of animal feed crops in the Bobane Igo area can support food security and increase the income of breeders in the area.